2013
DOI: 10.1155/2013/863240
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Inoculants and Their Impact on Soil Microbial Communities: A Review

Abstract: The knowledge of the survival of inoculated fungal and bacterial strains in field and the effects of their release on the indigenous microbial communities has been of great interest since the practical use of selected natural or genetically modified microorganisms has been developed. Soil inoculation or seed bacterization may lead to changes in the structure of the indigenous microbial communities, which is important with regard to the safety of introduction of microbes into the environment. Many reports indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
188
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(198 citation statements)
references
References 87 publications
5
188
3
2
Order By: Relevance
“…Some rhizosphere microbiome inoculations could modify bacterial communities and change plant flowering time (Panke-Buisse et al 2015). R. gallicum 8a3 and E. meliloti 4H41 inoculation showed significant effects on bacterial structure and diversity in the bulk soil of common bean (Trabelsi and Mhamdi 2013). In this study, we investigated the effect of G. liquefaciens qzr14 inoculation on bacterial community in rhizosphere and bulk soil simultaneously.…”
Section: The Effects Of G Liquefaciens Qzr14 Inoculation On Soil Bacmentioning
confidence: 99%
See 2 more Smart Citations
“…Some rhizosphere microbiome inoculations could modify bacterial communities and change plant flowering time (Panke-Buisse et al 2015). R. gallicum 8a3 and E. meliloti 4H41 inoculation showed significant effects on bacterial structure and diversity in the bulk soil of common bean (Trabelsi and Mhamdi 2013). In this study, we investigated the effect of G. liquefaciens qzr14 inoculation on bacterial community in rhizosphere and bulk soil simultaneously.…”
Section: The Effects Of G Liquefaciens Qzr14 Inoculation On Soil Bacmentioning
confidence: 99%
“…G. liquefaciens qzr14 inoculation had significant positive effects on bacterial diversity and biomass. Several reports indicated that the application of microbial inoculants can influence, at least temporarily, the resident microbial community's composition and function by directly inducing trophic competitions and antagonistic/ synergic interactions with resident microbial populations or indirectly mediating via enhanced root growth and exudation (Trabelsi and Mhamdi 2013). It was inferred that the introduced G. liquefaciens qzr14 effectively colonized the rhizosphere soil of cucumber and then expanded the rhizosphere bacterial communities by solubilizing soil phosphorus and supplying soluble phosphorus (Fig.…”
Section: The Effects Of G Liquefaciens Qzr14 Inoculation On Soil Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculation with mixed different strains could be an alternative to inoculation with individual strains, likely reflecting the different mechanisms used by each strain in the consortium [173]. Combined inoculation with N 2 -fixing and phosphate solubilizing bacteria were more effective than a single microorganism for providing a more balanced nutrition for plants [19,174].…”
Section: Co-inoculation Of Multiple Pgprsmentioning
confidence: 99%
“…Microorganisms in the rhizosphere play the role of intermediary between plants and soil, establishing complex interrelationships throughout the vegetation period and can perform functions such as soil improvement, degradation of pollutants and removal of dangerous compounds from ecosystem (Arora, 2015, Sandor et al, 2016. Rhizosphere control is a key process in mechanisms needed to solve critical issues facing the planet, including agriculture, improvement of water quality, climate change mitigation and biodiversity conservation (Trabelsi and Mhamdi, 2013).…”
Section: Introductionmentioning
confidence: 99%